Household Costs of Diarrhea by Etiology in 7 Countries, The Global Enterics Mulitcenter Study (GEMS). (3rd April 2019) - Zimmermann, Marita; Kotloff, Karen; Nasrin, Dilruba; Roose, Anna; Levine, Myron M; Rheingans, Richard; Farag, Tamar; Walker, Damian; Pecenka, Clint
Abstract: Background: Although there are many overlapping features, pediatric diarrheal diseases can vary in severity, duration, clinical manifestations, and sequelae according to the causal pathogen, which in turn can impact the economic burden on patients and their families. We aimed to evaluate the household costs of diarrheal disease by pathogen in 7 countries. Methods: We analyzed data from the Global Enteric Multicenter Study (GEMS), a prospective, age-stratified, matched case–control study of moderate to severe diarrheal disease among children aged 0–59 months in 7 low-income countries; 4 in Africa (Kenya, Mali, Mozambique, The Gambia) and 3 in Asia (Bangladesh, India, Pakistan). Demographic, epidemiological, economic, and clinical data were collected, and a stool sample was obtained for microbiological analysis at enrollment. We used a multivariate generalized linear model to assess the effect of rotavirus, Cryptosporidium, heat-stable toxin (ST)–producing enterotoxigenic Escherichia coli (ETEC [ST only or LT plus ST]), Shigella, Campylobacter jejuni, norovirus GII, Vibrio cholerae O1, age, gender, in/outpatient, and country on total costs to the patient/family. Results: Household out-of-pocket costs were higher in Mali than any other country. Within countries, household cost differences between pathogens were minimal and not statistically significantly different. Conclusions: We found no significant differences in household costs by pathogen. Despite data limitations, understanding pathogen-specific household costs (or lack thereof) is useful, as decision-makers could consider broader illness cost information and its relevance to a particular pathogen's economic burden and contribution to poverty when deciding which pathogens to target for interventions.